1994
DOI: 10.1159/000113586
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of Visual and Somatic Growth in the Rainbow Trout <i>Oncorhynchus mykiss</i>

Abstract: Hatchery reared juvenile rainbow trout of common parentage were reared on measured low or high rations, or fed ad libitum for 4.3 months to produce fish with different growth rates. Fish from the different groups differed in size by up to 40 and 290% for length and weight, respectively, by the end of the trial. Slow somatic growth was not accompanied by correspondingly slow growth of either the eyes, optic tectum or the cerebellum, suggesting that above a certain maintenance ration, growth of these parts of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 5 publications
(7 reference statements)
1
26
1
1
Order By: Relevance
“…Montgomery et al (1997) showed with the Antarctic silverfish (Pleuragramma antarcticum) that eye growth and somatic growth are on separate trajectories, and the breaks in the relative eye diameter result from overwinter periods when somatic growth is static but the eye continues to grow. Similar results were found in the rainbow trout Oncorhynchus mykiss (Pankhurst and Montgomery, 1994). Moreover, carp pituitary extract together with a dopamine antagonist caused an increase in eye size and significant gonadal development in the female of Anguilla anguilla in wild and cultivated stocks (Muller et al, 2003).…”
Section: Discussionsupporting
confidence: 81%
“…Montgomery et al (1997) showed with the Antarctic silverfish (Pleuragramma antarcticum) that eye growth and somatic growth are on separate trajectories, and the breaks in the relative eye diameter result from overwinter periods when somatic growth is static but the eye continues to grow. Similar results were found in the rainbow trout Oncorhynchus mykiss (Pankhurst and Montgomery, 1994). Moreover, carp pituitary extract together with a dopamine antagonist caused an increase in eye size and significant gonadal development in the female of Anguilla anguilla in wild and cultivated stocks (Muller et al, 2003).…”
Section: Discussionsupporting
confidence: 81%
“…3,4). Allometric growth in eye size (Pankhurst & Montgomery 1994) probably explains the comparatively large eye in the small specimens, and the difference in eye size between the larger and small Chathams fish.…”
Section: Eye Diametermentioning
confidence: 98%
“…Pankhurst and Montgomery (1994) found that growth of the eye is maintained at the expense of low somatic growth during suboptimal rearing conditions that could help to explain the fact that no differences in cataract formation was seen albeit there were major ammonia-related growth differences. The unilateral eye changes indicate a mechanical causation compared to often bilateral nutritional-related changes (Waagbø et al 2010).…”
Section: Discussionmentioning
confidence: 97%